Role of vasoactive intestinal peptide in the light input to the circadian system. (25th May 2015) - Vosko, Andrew; van Diepen, Hester C.; Kuljis, Dika; Chiu, Andrew M.; Heyer, Djai; Terra, Huub; Carpenter, Ellen; Michel, Stephan; Meijer, Johanna H.; Colwell, Christopher S.
Abstract The neuropeptide vasoactive intestinal peptide (VIP) is expressed at high levels in a subset of neurons in the ventral region of the suprachiasmatic nucleus (SCN). While VIP is known to be important for the synchronization of the SCN network, the role of VIP in photic regulation of the circadian system has received less attention. In the present study, we found that the light‐evoked increase in electrical activity in vivo was unaltered by the loss of VIP. In the absence of VIP, the ventral SCN still exhibited N‐methyl‐d‐aspartate‐evoked responses in a brain slice preparation, although the absolute levels of neural activity before and after treatment were significantly reduced. Next, we used calcium imaging techniques to determine if the loss of VIP altered the calcium influx due to retinohypothalamic tract stimulation. The magnitude of the evoked calcium influx was not reduced in the ventral SCN, but did decline in the dorsal SCN regions. We examined the time course of the photic induction of Period1 in the SCN using in situ hybridization in VIP‐mutant mice. We found that the initial induction of Period1 was not reduced by the loss of this signaling peptide. However, the sustained increase in Period1 expression (after 30 min) was significantly reduced. Similar results were found by measuring the light induction of cFOS in the SCN. These findings suggest that VIP is critical for longer‐term changes within the SCN circuit, but does not play a role in the acute light response.